Unimolecular antiparallel G-quadruplex folding topology of 2'-5'-isoTBA sequences remains unaltered by loop composition - Aher, Manisha N. (Organic & Biomolecular Chemistry, 2015)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> A 2'-5'-linked isoTBA 15 mer sequence with (232) loop composition formed stable antiparallel quadruplex structures similar to the SELEX derived 15 mer TBA sequence with (232) loop composition. A parallel versus antiparallel topology of 3'-5'-G-quadruplexes is largely dictated by the loop length, and it is known that the truncated loops favour parallel quadruplexes. In contrast to TBA, systematic reduction of the loop length in isoTBA from (232) to (222), (131) or even (111) did not alter the antiparallel topology of the resulting 14 mer, 13 mer and 11 mer G-rich modified isoTBA-like sequences.

Influence of fluorine substitution on the molecular conformation of 3 `-deoxy-3 `-fluoro-5-methyluriaine - Aher, Manisha N.; Erande, Namrata D.; Kumar, Vaijayanti A.; Fernandes, Moneesha; Gonnade, Rajesh G. (Acta Crystallographica Section C-Structural Chemistry, 2020)
{Fluorine substitutions on the furanose ring of nucleosides are known to strongly influence the conformational properties of oligonucleotides. In order to assess the effect of fluorine on the conformation of 3'-deoxy-3'-fluoro-5-methyluridine (T-R(F)), C-10 H13FN2O5, we studied its stereochemistry in the crystalline state using X-ray crystallography. The compound crystallizes in the chiral orthorhombic space group P2(1)2(1)2(1) and contains two symmetry-independent molecules (A and B) in the asymmetric unit. The furanose ring in molecules A and B adopts conformations between envelope (E-2, 2'-endo
Keywords: crystal structure; fluoro nucleoside; pseudorotation parameter; sugar puckering; uridine